Dodging the Communications Decency Act when Analyzing Libel Liability of On-line Services: Lunney v. Prodigy Treats Service Provider like Common Carrier Rather than Address Retroactivity Issue - Fried, Neil (Science and Technology Law Review, 1999)
Dodging the Communications Decency Act when Analyzing Libel Liability of On-line Services discusses the on-line libel case of Lunney v. Prodigy. In that case, the Appellate Division of the N.Y. Supreme Court treated Prodigy like a common carrier rather than apply provisions of the Communication Decency Act that prohibit treating interactive computer services as publishers of third-party speech. The court appears to have done so to avoid reaching issues regarding retroactive application of the CDA. The article discusses the Appellate Division’s analysis, and concludes that the court’s decision to sidestep the CDA and to compare service providers to common carriers was unwise. In the process, the article addresses four seminal on-line libel cases—Cubby, Inc. v. CompuServe, Inc.; Stratton Oakmont, Inc. v. Prodigy Servs. Co.; Zeran v. America Online, Inc.; and Blumenthal v. Drudge—as well as the libel-related provisions of the CDA. Lastly, the article makes recommendations to the N.Y. Court of Appeals, which heard oral arguments October 13, 1999, in an appeal of the case.